THE ROLE OF 4K COMPETENCIES IN ENHANCING LITERACY DEVELOPMENT: INSIGHTS FROM INTERNATIONAL PRACTICE - Allaberganova Marifat Kuranbayevna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Abstract: The rapid transformation of global education systems has placed increasing emphasis on the integration of 4K competencies—critical thinking, creativity, communication, and collaboration—into literacy development frameworks. This article explores how international educational practices incorporate these competencies to enhance literacy outcomes among learners. Drawing on global benchmarks such as OECD and large-scale assessments like PISA, the study examines pedagogical innovations, curriculum reforms, and classroom strategies that foster both traditional and functional literacy. The findings suggest that embedding 4K skills within literacy instruction significantly improves learners’ cognitive engagement, adaptability, and communicative competence in diverse contexts.